Which income comparisons matter to people, and how? Evidence from a large field experiment - Xiaogeng Xu; Satu Metsälampi; Michael Kirchler; Kaisa Kotakorpi; Peter Hans Matthews; Topi Miettinen (Helsinki Graduate School of Economics, 2023)
Received wisdom holds that income rank matters for life satisfaction. In much of the literature, however, income comparisons are limited to the national population and evidence is correlational. In this paper, we investigate differences in the causal effects of rank information across reference groups. In a representative sample of mid-career Finns, we randomize individuals to receive personal rank information about educational, municipal, occupational, or age reference groups, and compare the effects, for a set of alternative welfare measures, to the standard national reference group and to a control group that receives no information. We also characterize the accuracy of rank beliefs across groups. Our data, which integrates experimental and register data, finds that rank information causes differences in satisfaction with disposable income, perceived fairness of own income, and wage satisfaction, but not life satisfaction. We also find substantial variation in the effects across reference groups, with those for the national reference group both weak and insignicant.
Keywords: D63; D8; D91; I31; 330; relative position; individual welfare; fairness; comparison group; information provision